(untitled) (Revista Brasileira de História da Educação, 2012)
MONARCHA, Carlos. Brasil arcaico, Escola nova: ciência, técnica e utopia nos anos 1920-1930. São Paulo, SP: Editora da UNESP, 2009. 342p. ISBN 9788571399082.